Habitat vulnerability for the Nile crocodile (Crocodylus niloticus) in the Okavango Delta, Botswana - Shacks, Vincent (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MA (Geography and Environmental Studies))--University of Stellenbosch, 2006.